#wegmit219a: Governmental Restrictions and the Importance of Online Hashtags in Feminist Movements - Penning, Anne Laura (Satura, 2020)
“The personal is political”—this slogan, that became popular by U.S. American feminist movements in the 1960s to highlight the connection between individual experiences and political structures (McCann and SeungKyung 191), appears to be gaining momentum again, this time in the context of online movements. With social media widely accessible, the personal becomes not only political but also something to post about, as seen with recent hashtag movements like #metoo. A similar feminist protest movement started in Germany in 2017, introducing the hashtag #wegmit219a to voice discontent regarding Germany’s Abortion Act. Almost 30 years after Germany’s reunification, the debate regarding the abortion legislation in the German Penal Code thus resurfaces. Similar to former debates between East and West Germany around 1990 focusing particularly on §219a that prohibits the “promotion” of abortions, therefore e.g. banning any information on websites indicating even the possibility of an abortion, current protests and social media movements also centre on said paragraph and aim at abolishing it with the help of internet campaigns (“Weg Mit §219a”). This paper will primarily focus on #wegmit219a movement and discuss whether its online discourse presents a useful tool to provoke change within the German legal system. Drawing on the origin and the development of the §219a, I argue that the Abortion Act exemplifies Germany’s antiquated stance on womanhood in opposition to Germany’s image as a self-proclaimed progressive and liberal state.